Litter quality assessed by solid state 13C NMR spectroscopy predicts decay rate better than C/N and Lignin/N ratios - Bonanomi, Giuliano; Incerti, Guido; Giannino, Francesco; Mingo, Antonio; Lanzotti, Virginia; Mazzoleni, Stefano (Soil Biology and Biochemistry, 2013)
Predictions of litter decomposition rates are critical for modelling biogeochemical cycling in terrestrial ecosystems and forecasting organic carbon and nutrient stock balances. Litter quality, besides climatic conditions, is recognized as a main factor affecting decay rates and it has been traditionally assessed by the C/N and lignin/N ratios of undecomposed materials. Here, solid state 13 C NMR spectroscopy and proximate chemical analysis have been used to characterize litter organic C in a litterbag experiment with 64 different litter types decomposing under controlled conditions of temperature and water content. A statistical comparative analysis provided evidence that C/N and lignin/N ratios, showing different trends of correlation with decay rates at different decomposition stages, can be used to describe the quality of undecomposed litter, but are unable to predict mass loss of already decomposed materials. A principal component regression (PCR) model based on 13 C NMR spectra, ﬁtted and cross-validated by using either two randomly selected sets of litter types, showed highly ﬁtting predictions of observed decay rates throughout the decomposition process. The simple ratio 70e75/52e57 corresponding to Oalkyl C of carbohydrates and methoxyl C of lignin, respectively, showed the highest correlation with decay rate among different tested parameters. These ﬁndings enhance our understanding of litter quality, and improve our ability to predict decomposition dynamics. The 13 C NMR-based 70e75/52e57 ratio is proposed as an alternative to C/N and lignin/N ratios for application in experimental and modelling work
The following values have no corresponding Zotero field: publisher: Elsevier Ltd
Keywords: C stocks; C-cycle; decomposition; litter quality; litterbag; Principal component regression; Proximate cellulose and lignin

Tree Species Effect on Litter Decomposition and Nutrient Release in Mediterranean Oak Forests Changes Over Time - Aponte, Cristina; García, Luis V.; Marañón, Teodoro (Ecosystems, 2012)
ree species can affect the decomposition process through the quality of their leaf fall and through the species-speciﬁc conditions that they generate in their environment. We compared the relative importance of these effects in a 2-year experiment. Litterbags containing leaf litter of the winter-deciduous Quercus canariensis, the evergreen Q. suber and mixed litter were incubated beneath distinct plant covers. We measured litter carbon loss, 9 macro- and micronutrients and 18 soil chemical, physical and biological parameters of the incubation environment. Tree species affected decay dynamics through their litter quality and, to a lesser extent, through the induced environmental conditions. The deciduous litter showed a faster initial decomposition but left a larger fraction of slow decomposable biomass compared with the perennial litter; in contrast the deciduous environment impeded early decomposition while promoting further carbon loss in the latter decay stages. The interaction of these effects led to a negative litter–environment interaction contradicting the home-ﬁeld advantage hypothesis. Leaf litter N, Ca and Mn as well as soil N, P and soil moisture were the best predictors for decomposition rates. Litter N and Ca exerted counteractive effects in early versus late decay stages; Mn was the best predictor for the decomposition limit value, that is, the fraction of slowly decomposable biomass at the later stage of decomposition; P and soil moisture showed a constant and positive relation with carbon loss. The deciduous oak litter had a higher initial nutrient content and released its nutrients faster and in a higher proportion than the perennial oak litter, signiﬁcantly increasing soil fertility beneath its canopy. Our ﬁndings provide further insights into the factors that control the early and late stages of the decomposition process and reveal potential mechanisms underlying tree species inﬂuence on litter decay rate, carbon accumulation and nutrient cycling.
Keywords: decomposition limit value; Lignin; litter chemistry; litterbag; Plant–soil interactions; Quercus; Soil fertility